Solar Charge Station (SCS) Application for Recharging Electric Sprayer Batteries in Bone Regency - Rudi Amme; Nasaruddin Salam; Ilyas Renreng; Jalaluddin .; LH Arma; Hairul Arsyad; Azwar Hayat; Asriadi Sakka; Izzul Islam (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2026)
This community service initiative was carried out to provide a practical solution to the problem of charging electric sprayers, a common challenge faced by farmers in Bone Regency. This region has abundant solar energy potential, yet it has not been optimally utilized to support agricultural activities. The program implements Solar Charge Stations (SCS) as an alternative source of clean energy that farmers can use independently without relying on the national power grid. Activities included education, training on SCS installation and assembly, and SCS maintenance. Pre-test results showed that the majority of participants did not understand the material related to solar charge stations (SCS), with the “do not understand” category reaching 80–92% across all indicators. Only 8–12% of participants fell into the “understand” category. After the training was conducted, post-test results showed a significant improvement, with all participants moving to the “understand” and “fully understand” categories. For the renewable energy utilization indicator, 68% of participants were in the “very well understand” category, while for the SCS assembly and operation indicators, 88% and 80% respectively were in the “understand” category. This indicates that the training was effective in improving participants’ knowledge and skills.